Climatological patterns over South America derived from COSMIC radio occultation data - Hierro, R. (2012)
Meteorological phenomena are closely linked to the presence of water vapor. They mainly originate and develop in the troposphere, where almost all the atmospheric water is concentrated. The Global Positioning System radio occultation (GPS RO) technique provides vertical profiles of refractivity from which other properties such as temperature and water vapor can be derived. The GPS RO capability to reproduce global, synoptic, and regional climatological patterns over South America, which is a mostly oceanic continent, is tested. From FORMOSAT-3/COSMIC mission data (2006-2010), our previous knowledge regarding global and synoptic/regional patterns of temperature, equivalent potential temperature, specific humidity, and pressure is verified. Special cases such as baroclinic disturbances arriving at South American midlatitudes and storm events over a mountain region near the Andes are analyzed. The temporal evolution and the latitude-longitude distribution in several layers of the variables listed above are well described with this technique. Copyright 2012 by the American Geophysical Union.